Assessment of anti-Müllerian hormone levels in premenopausal patients with systemic lupus erythematosus. (March 2016) - Gasparin, A A; Souza, L; Siebert, M; Xavier, R M; Chakr, R M S; Palominos, P E; Brenol, J C T; Monticielo, O A
Objective: The ovarian reserve of patients with systemic lupus erythematosus (SLE) may be affected by disease activity and medication use. Studies have found that patients with SLE have similar fertility rates as healthy women of the same age. The goal of the present study was to investigate the ovarian reserve of patients with SLE by measuring anti-Müllerian hormone (AMH) levels, and compare it to that of healthy controls. Method: This was a case-control study performed on 80 premenopausal women, of whom 40 fulfilled the 1997 American College of Rheumatology (ACR) criteria for SLE and 40 healthy controls paired by oral contraceptive use. Serum concentrations of AMH in peripheral venous blood were measured using a human AMH ELISA kit (CUSABIO, Wuhan, China). Results: AMH serum levels did not differ between patients with SLE and controls (22.79 ± 17.32 ng/ml versus 21.41 ± 16.22 ng/ml, respectively, p  = 0.7), even after adjusting for age (21.03 ± 2.074 ng/ml versus 23.97 ± 2.71 ng/ml; p  = 0.5 ) . AHM levels were not significantly correlated with disease duration ( r  = 0.2; p  = 0.3), body mass index ( r  = 0.2; p  = 0.2) and disease activity (SLEDAI ( r  = 0.1; p  = 0.7)) and damage indices (SLICC ( r  = 0.1; p  = 0.7)). No associations were found between AMH and ethnicity, current smoking, as well as current or prior use of cyclophosphamide and other immunosuppressants. Conclusion: In this cross-sectional study, women with SLE demonstrated similar AMH levels as healthy controls, suggesting preserved ovarian reserve in this population.